Guy Fawkes : a Complete History of the Gunpowder Treason. - Lathbury, Thomas (AUK Classics, 5., 2010)
This excellent analysis of the famous 'Gunpowder Plot' by Thomas Lathbury has been specially formatted for today's e-readers. The account details the full history of one of England's most famous historical periods, including information about the characters involved, the political situation at the time and of course what happened to those involved. It is a fantastic account which will appeal both to those interested in history and of course lovers of intrigue and suspense.